OUTCOMES AND CHARACTERISTICS OF ROTATIONAL ATHERECTOMY IN A TERTIARY CARE HOSPITAL - Marryam Rauf; Ahmad Muqeet; Naila Altaf (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Objectives: A retrospective review of the short-term outcomes of rotational atherectomy in a high Syntax and high CathPCI Risk population.Methodology: A total of 40 patients who had rotational atherectomy between June, 2020 to November 2020 were reviewed retrospectively in Jinnah hospital lahore Institute of Cardiology, Lahore Pakistan, after ethical committee approval. The patients were followed-up clinically for major adverse cardiovascular events (MACE) and procedure success after three months.Results: Patients undergoing rotational atherectomy were at high risk with a mean NCDR CathPCI risk score of 50.2±11 and a mean Syntax score of 31.2 ± 6.24. The patients mean age was 68.2 ± 8.1 years, 81% were male, 80% were type 2 diabetics, 37.5% have chronic kidney disease and 27(67.5%) have >32 of syntax score. Of the 27 people, all except one person in the high-risk syntax group reported a successful procedure. After 3 months, 4 patients reported major adverse cardiovascular events. Of these three, one had died during the procedure and recurrent myocardial infarction was noticed in remaining two patients. These two patients refused revascularization and were medically treated. Even with revascularization; one patient expired. All patients with major adverse cardiovascular events syntax score>32.Conclusion: Despite increased Syntax score angioplasty with Rotaablation achieved good clinical outcomes with urgent percutaneous coronary intervention in calcified lesions with major adverse cardiovascular events.